2007
DOI: 10.1002/ajmg.a.32078
|View full text |Cite
|
Sign up to set email alerts
|

Muenke syndrome (FGFR3‐related craniosynostosis): Expansion of the phenotype and review of the literature

Abstract: Muenke syndrome is an autosomal dominant disorder characterized by coronal suture craniosynostosis, hearing loss, developmental delay, carpal and tarsal fusions, and the presence of the Pro250Arg mutation in the FGFR3 gene. Reduced penetrance and variable expressivity contribute to the wide spectrum of clinical findings in Muenke syndrome. To better define the clinical features of this syndrome, we initiated a study of the natural history of Muenke syndrome. To date, we have conducted a standardized evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 46 publications
6
104
2
2
Order By: Relevance
“…7 ). Muenke syndrome is additionally associated with strabismus, low-frequency hearing impairment (mostly sensorineural) with 20% requiring a hearing aid, carpal and tarsal synostosis, brachydactyly, thick straight hair, and neurodevelopmental delay [Doherty et al, 2007;de Jong et al, 2010;Johnson and Wilkie, 2011;Kruszka et al, 2016]. Seizures are identified as an association with Muenke syndrome, but not related to increased ICP, and a cause theorised as temporal anomalies [Grosso et al, 2003;Agochukwu et al, 2012b].…”
Section: Muenke Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…7 ). Muenke syndrome is additionally associated with strabismus, low-frequency hearing impairment (mostly sensorineural) with 20% requiring a hearing aid, carpal and tarsal synostosis, brachydactyly, thick straight hair, and neurodevelopmental delay [Doherty et al, 2007;de Jong et al, 2010;Johnson and Wilkie, 2011;Kruszka et al, 2016]. Seizures are identified as an association with Muenke syndrome, but not related to increased ICP, and a cause theorised as temporal anomalies [Grosso et al, 2003;Agochukwu et al, 2012b].…”
Section: Muenke Syndromementioning
confidence: 99%
“…Muenke syndrome was genetically described in 1997 [Muenke et al, 1997] and is now the most common syndromic presentation with a prevalence of 1 in 10,000-30,000 live births [Doherty et al, 2007;Wilkie et al, 2017]. This syndrome results from mutation c.749C>G in the FGFR3 gene, resulting in p.Pro250Arg [Muenke et al, 1997].…”
Section: Muenke Syndromementioning
confidence: 99%
“…9,12 Mean FSIQs of patients who have Muenke and Saethre-Chotzen syndrome ranged from 50 to 120. [12][13][14][15][16] No published studies were found on intellectual functioning in children who have complex craniosynostosis.…”
mentioning
confidence: 99%
“…It is caused by a mutation (Pro250Arg) of the FGFR3 gene, with autosomal dominant inheritance and variable clinical expression [16].…”
Section: Syndromal Craniosynostosesmentioning
confidence: 99%